Il rapporto uomo donna come confronto di identità: una riflessione sul periodo dal dopoguerra ad oggi - Ingrao, Giulia (Il sogno della farfalla, 2006)
This articles proposes an analysis of the changes which occurred in the conditions of women in Italy during the post-war periods of the 1st and 2nd World Wars. Changes related not only to having achieved equality with men both at work and within the family, but also to the overcoming of stereotypes in which the female image was entrapped and desirous of an identity that would permit an evolution of the male-female relationship. Progress made in the female condition starting from the Resistance including the achievements of the post-war period, without forgetting the freedom movements of 1968 and the 70s-80s, is considered. What becomes evident is the absence of research and a new way of thinking and understanding the mental reality of human beings. Vice versa, if we desire a true transformation we must learn to see the male-female relationship as two identities coming face to face with each other, where human sexuality does not constitute a reciprocal annulment nor an instinct for procreation, but a dialectic.